ANÁLISE DO IMPACTO DO TAMANHO E DA POSIÇÃO DAS ABERTURAS NO FLUXO DE AR: ENSAIOS NA MESA D´ÁGUA E SIMULAÇÕES CFD - Gularte, Izabella; Mizgier, Martin; Lukiantchuki, Marieli; Xavier, Ana Clara (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Natural ventilation is one of the most important strategies for the passive thermal conditioning of buildings up to 85% of the year for the hottest cities in Brazil. The size, shape and location of the openings in the building have a significant impact on the performance of the internal airflow. Therefore, the objective of this article is to evaluate the impact of the size and position of openings in the internal airflow of buildings. The methodology used is the comparison between experimental tests in the water table and simulation through Computational Fluid Dynamics (CFD). The results indicate that the size and location of openings are very important to the performance of natural ventilation. Besides this, it is possible to note that both tools are very useful to the study of natural ventilation, presenting a compatibility of the physical phenomena and very similar results.